THE EFFECTIVENESS OF “CALMING BABY TIPS” IN OVERCOMING CRYING BABIES - Regina Vidya Trias Novita; Nunik Yuli Astuti; Wilhelma Susilo (Journal of Maternity Care and Reproductive Health, 2018)
Calming baby or 5S’s tips can be done using steps such as swaddling, tilting baby (Side or stomach position), shshshs (shushing), swinging and sucking. These interventions support the success of breastfeeding and reduce women’s stress and depression during the puerperium. This  method is also intended to make the child's growth grow optimally because of the child's energy is fulfilled in the growth period. The purpose of this study was to find out 5S's effectiveness to calm babies when babies cry. The study was conducted in March-August 2016, with a sample of 250 post-partum women in the intervention group and 85 in the control group. This study used quantitative methods with quasi-experimental design and Binary Logistic Regression approach. The results showed that maternal characteristics were not significant (pvalue> 0.05) with the incidence of babies stopping crying. Nagelkerke R square values showed variables such as maternal age, parity, type of labor, education, and work affecting 15.9 times in the calming baby intervention tips so the baby stopped crying. Type of labor was significant to the incidence of babies stopping crying using calming baby tips with a p-value of 0.000. The results of the interval estimation (95%) concluded that the calming baby tips after the intervention was 0.194 to 0.62. This intervention in calming baby tips was effective in stopping crying babies (P Value 0.021). The calming baby tips can be used as educational material for postpartum women.  Keywords: 5S's, shushing, sucking, swaddling, swinging.